Sistem sokongan pensyarah FSKTM Universiti Malaya / Azahari Omar - Azahari , Omar (2000)
"Sistem Sokongan Pensyarah" (SISOP) is a final project that is carried out after - its Importance was admitted by supervisor, Pn . Salimah Mokhtar . This system is important in keeping all activity including an activity among lecturer inside or outside of university. Activities that is carried out by lecturer such as publications, conferences, research which is like its involvement in the teaching field, consultancies and etc. All of these information are very important but there is no an alternative to develop this system before. As its objective, when this system is ready to use, it just not only keep the information that relates with the lecturer itself. but it also can easily achieve by the user. Prototype model has been used for this approach because it is matching with this system. From this model, all step of task that is implemented can be altered to return according to user latest necessity From characters of system, hope this system can settle problem related to the lecturer as a system user and the involvement of lecturer in every matter can be exposed to the entire University of Malaya member and also its general off-campus to raise the excellency of University of Malaya.